The scene of culture and consciousness II - Gans, Eric Lawrence (2023)
We may say that the scene of consciousness, or scene of representation, is in itself paradoxical. For if consciousness is an individual phenomenon, such that its extension to groups is always metaphoric, the scene, on the other hand, is essentially collective, so that a scene in which there is only one subject is itself something...